L’union du masque et du corps des super-héros : nudités des Watchmen (2019) - Guillaume Dulong (Mise au Point)
In 2019, screenwriter Damon Lindelof will direct his major project, the audiovisual adaptation of Dave Gibbons and Alan Moore’s comic book, Watchmen. Watchmen re-reads superheroic mythology as the flipside and legend of the contradictions of an American society that is individualistic and liberal, imperialist and democratic. The television adaptation is both a sequel and a return to the origins of the comic book universe. At the same time, it is a critique of the way in which America writes its own history. The plot takes place in an alternate reality but opens on a real event: the race riots and massacre of African-Americans in Tulsa on 31 May and 1 June 1921. The narrative reinterprets the prohibitions of history (fiction and historiography), what must not be said and what is between the lines, between the boxes of the comic: the systemic persecution and invisibilisation suffered by the African-American minority.Lindelof sees the super-heroic representation of watchmen subjectivity as a will to power or monster love. She is a "monster" because of the double entendre of watch: she looks and is seen (watch). She is a 'monster', too, in that she plays the watch as she recounts her apocalypse. Gibbons and Moore have already presented the process of superheroic subjectivation, or even of the Nietzschean Übermensch as a Body. They turned it into an ideological version of the subjectivity of the normal man as a man of resentment: the identity troubles of masked (or unmasked) heroes questioned the persona incarnation of the contemporary subject. The heroes were thus plagued by the "watchmen question", inspired by Juvenal's "Quis custodiet ipso custodes" (Who watches the watchmen?).The series radicalises the ambivalence of this reading of the superhero as a power-hungry mask and a body bursting with power. On the one hand, it exhibits the power apparatus and latent racism of the aforementioned mythology as an instrument for regulating a society of panoptic control, that of the Cyclops organisation, guardian of a xenophobic norm. On the other hand, Lindelof claims to give a voice, an image and a body back to the traumatised and abnormal, nurturing a resistant and powerful subjectivity: blue nudity. This is how Lindelof presents us with a capitoline triad to unmask: Hooded Justice/William Reeves (Louis Gossett Jr), Sister Night/Angela Abar (Regina King) and Dr Manhattan/Calvin Abar/Jon Osterman (Yahya Abdul-Mateen II).